Shaping Trust through Argument Quality: Exploring its Impact on Purchase Intentions in Social Commerce - Kenang, Irantha Hendrika; Kasetty, Donald Michi (Bina Nusantara University, 2024)
The research aimed to investigate the influence of argument quality, namely perceived informativeness and persuasiveness, on trust and purchase intention within a social commerce context, focusing on TikTok. A quantitative method was applied, including 150 respondents. Participants were selected based on specific criteria of being active social commerce users. Additionally, the participants’ age was restricted to between 18 and 23 years old since data indicated that Generation Z with a strong tendency to shop online, used TikTok more than other social media platforms. Data collection included distributing questionnaires through Google Forms, using a 5-point Likert scale. Data analysis was conducted using Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results show that perceived informativeness and persuasiveness affect trust towards both members of TikTok and the platform. It has a positive impact on purchase intention due to higher levels of trust in social commerce members and the platform. Meanwhile, trust towards members significantly affects the TikTok platform, and the relationship is non-significant. A potential differentiation is reported concerning the formation of trust. In this context, trust in individual users does not necessarily influence the platform within the context of TikTok social commerce. These insights are valuable for marketers and platform developers seeking to improve user engagement and transaction rates on social commerce platforms. The implications suggest that enhancing the informativeness and persuasiveness of content can be a strategic method for enhancing trust and promoting purchase intention.